Nilai-Nilai Kebudayaan Seni Kriya Antara Ekspresi Dan Desain - Kusmadi Kusmadi (Ornamen, 2008)
Culture as a result of human activities in their life and it is a reflection of the level of their ages. One of subculture is art, including fine arts which containing craft arts. The results of this art can be practical functional, aesthetics and also as an expression/symbolic work of the creator, in nature.The expression of craft arts is highly bound by its elaborate materials, technical or process. The realization requires for technical sckill, persevere and patience, and also it can be done in short way, while it can be arranged/ordered so that the expression exposures can be touchable for them who observe them.The craft design can also be understood as the design approach both in methodology, principal and objective of design, both in relation with the practical functional, aesthetics and also symbolic aspects.One of the characteristic of the craft arts is its concrete outcome of the ability or skill from the creator (craftmanship) on the form or shape of their works in high quality, both in uniqueness, aesthetics, philosophy, symbolic and also practical function aspects viewpoints. The craftman can use any simple equipment, even with relatively modern technology in hands to realize them, but the control still on their own bare hands.Keyword : expression,symbolic,craft, design